Effect of hyperoxia on critical power and V.O2 kinetics during upright cycling - Goulding, R. P.; Roche, D. M.; Marwood, S. (Medicine & Science in Sports & Exercise, 2020)
Introduction/Purpose Critical power (CP) is a fundamental parameter defining high-intensity exercise tolerance; however, its physiological determinants are incompletely understood. The present study determined the impact of hyperoxia on CP, the time constant of phase II pulmonary oxygen uptake kinetics (tV.O2), and muscle oxygenation (assessed by near-infrared spectroscopy) in nine healthy men performing upright cycle ergometry.